Bardet-Biedl syndrome in two sisters: A rare incidence - Varma, Chaitanya; Bhat, Ramesh Y.; Bhatt, Sonia (Journal of Pediatric Genetics, 2013)
Bardet-Biedl syndrome is an autosomal recessive disorder characterized by retinitis pigmentosa, obesity, polydactyly, mental retardation and hypogonadism. We present two sisters with this rare genetic condition.
Keywords: Bardet-Biedl; hypogonadism; polydactyly; retinal dystrophy; sibling